Legal Protection for Children as Victims of Sexual Violence - Itok Dwi Kurniawan (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
One of the crimes that has become a recent phenomenon is sexual violence, especially against children. Children are an invaluable gift given by God to every human couple to be cared for, protected and educated well. He is a human being who has limited physical, mental and social abilities to overcome the various risks and dangers he faces and also automatically still depends on other parties, especially family members who play an active role in protecting and looking after him. The nature of this research is descriptive analysis, meaning that from this research it is hoped that a detailed and systematic picture of the problems to be studied will be obtained. The intended analysis is based on descriptions, the facts obtained will be subjected to careful analysis to answer the problem. So that you can answer questions according to the main problem in this writing. This research was carried out using data collection tools, namely: literature study or document study (documentary study) to collect secondary data related to problems in the protection of child victims of sexual violence. In the form of legal protection for children victims of sexual crimes are legal assistance, rehabilitation, health services and social security in accordance with physical, mental, spiritual and social needs as an effort to restore the condition of children victims of sexual violence who have long-term trauma. Obstacles in providing legal protection for child victims of sexual crimes are legal substance, legal structure, legal culture, and facilities and infrastructure that are not yet running optimally.